‘There’s something about admitting that you are lonely’ – prevalence, impact and solutions to loneliness in terminal illness: An explanatory sequential multi-methods study - Hanna, Jeffrey R; McConnell, Tracey; Harrison, Craig; Patynowska, Katarzyna A; Finucane, Anne M; Hudson, Briony; Paradine, Sharon; McCullagh, Angela; Reid, Joanne (Palliative medicine, 2022)
Background: Loneliness is a prevalent societal issue and can impact on a person’s physical and mental health. It is unclear how loneliness impacts on end of life experiences or how such feelings can be alleviated. Aim: To explore the perceived prevalence, impact and possible solutions to loneliness among people who are terminally ill and their carers in Northern Ireland through the lens of health and social care professionals. Design: An explanatory multi-method study. Setting/participants: An online survey (n = 68, response rate 30%) followed by three online focus groups with palliative and end of life care health and social care professionals (n = 14). Data were analysed using descriptive statistics and thematic analysis. Results: Loneliness was perceived by professionals as highly prevalent for people with a terminal illness (92.6%) and their carers (86.8%). Loneliness was considered a taboo subject and impacts on symptoms including pain and breathlessness and overall wellbeing at end of life. Social support was viewed as central towards alleviating feelings of loneliness and promoting connectedness at end of life. Four themes were identified: (1) the stigma of loneliness, (2) COVID-19: The loneliness pandemic (3) impact of loneliness across physical and mental health domains and (4) the power of social networks. Conclusion: There is a need for greater investment for social support initiatives to tackle experiences of loneliness at end of life. These services must be co-produced with people impacted by terminal illness to ensure they meet the needs of this population.